Advokasi Hukum Keluarga Islam Hukum Nikah Siri Tinjauan Yuridis dan Implikasi Sosial - Febriansah, Rido; Jasson, Royan; Pratama, Rizky; Noveri, Irsadanus; Syamsiah, Syamsiah (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Unregistered marriages are still a reality that is often found in Indonesian society. Although considered valid according to religion, these unregistered marriages cause serious problems in the legal realm, especially for women and children involved in them. The absence of legal documents makes their legal position very weak, women find it difficult to claim a living or legal protection, while children lose their rights to identity, recognition of lineage, and even inheritance. In the midst of this complexity, the state has not been fully present to provide adequate protection. This study aims to understand in more depth how the practice of unregistered marriages impacts the rights of women and children, and how the legal system and state policies respond to these issues. The study was conducted using a qualitative approach through normative and empirical legal methods. Data were collected through literature studies, legal documentation, and limited interviews with women who were perpetrators or victims of unregistered marriages. The results of the analysis were then interpreted thematically to see the patterns of problems that emerged. The results of the study showed that unregistered marriages not only caused legal inequality, but also showed deep social injustice. Women and children were the parties most affected by the absence of marriage registration. Meanwhile, the marriage confirmation mechanism which should have been a solution has instead turned into a general procedure that is widely legalized. This study recommends that the state strengthen the marriage registration system, increase legal literacy in society, and build legal protection that is more inclusive and pro-vulnerable groups.